Public management: analysis of the development of electronic government in the public administration of Ecuador in the period 2014-2016 - Osejo Domínguez, Edgar Efraín (2018)
States at the global level have been making efforts to improve Public Management at all levels, so that the use of Information and Communication Technologies (TIC) has helped to achieve this aim, allowing for better governance, has incorporated the term Electronic Government (GE). In Ecuador, the National Government through the National Secretary of Public Administration (SNAP) had the competence to implement, regulate, advise and support the implementation of GE, currently has the Ministry of Telecommunications and the MINTEL Information Society. The National Electronic Government Plan was generated for the period 2014 - 2017, establishing a legal and regulatory framework that allows compliance with international agreements. The regulatory framework has been institutionalized GE is now a state policy. The research seeks to carry out an evolutionary analysis of the development of GE in public administration in 33 public entities, using the Multi-Dimensional Model of Electronic Government Measurement for Latin America and the Caribbean proposed by CEPAL.